Supply, installation, testing and commissioning of 2 Nos. of 2500 KVA and 1 No. of 3150 KVA substation equipment, HT panel and LT panel etc. for Brac University new campus building, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Adex Corporation Ltd. to supply, installation, testing and commissioning of 2 Nos. of 2500 KVA and 1 No. of 3150 KVA substation equipment, HT panel and LT panel etc. for Brac University new campus project.